Neural Network Controller for Power Electronics Circuits - K.J. Rathi; M. S. Ali (Institute of Advanced Engineering and Science, 2017)
Artificial Intelligence (AI) techniques, particularly the neural networks, are recently having significant impact on power electronics. This paper explores the perspective of neural network applications in the intelligent control for power electronics circuits. The Neural Network Controller (NNC) is designed to track the output voltage and to improve the performance of power electronics circuits. The controller is designed and simulated using MATLAB-SIMULINK